2015
DOI: 10.1139/as-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Mercury concentrations in multiple tissues of Arctic Iceland Gulls (Larus glaucoides) wintering in Newfoundland

Abstract: Anthropogenic mercury (Hg) emissions are increasing and are potentially of concern for Arctic-nesting seabirds, particularly those that spend part of their year near dense human habitation. Iceland Gulls (Larus glaucoides B. Meyer, 1822) breed in the eastern Canadian Arctic and spend the majority of winter in towns and cities in eastern Newfoundland. We measured Hg in breast feathers, blood plasma, and red blood cells of Iceland Gulls wintering in and around St. John's, Newfoundland and Labrador, from 2011 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Metals such as arsenic (As), mercury (Hg), cadmium (Cd), copper (Cu), chromium (Cr), lead (Pb), iron (Fe), manganese (Mn) and zinc (Zn) do not degrade and these metals could easily accumulate throughout the trophic chain and persist in nature (Borchert, Leaphart, Bryan, & Beasley, 2019; Burger, Mizrahi, Tsipoura, Jeitner, & Gochfeld, 2018; Vizuete et al, 2018); at the same time, As, Cd, Pb and Hg have no established biological functions and are considered as contaminants (Hejna et al., 2018). The presence of HMs has been registered in tissues of wild birds (Bond & Robertson, 2015; Burger et al., 2018; Majidi, Bahramifar, & Ghasempouri, 2015; Sepúlveda & Gonzalez‐Acuña, 2014), including the Andean condor (Di Marzio et al., 2018; Plaza et al, 2019; Wiemeyer et al., 2017). Due to the HM toxicity to different organisms, bacteria have developed some resistance mechanisms and have managed to persist in various highly contaminated locations, constituting possible biomarkers of environmental contamination (Di Cesare, Eckert, & Corno, 2016; Martins, Zanetti, Pitondo‐Silva, & Stehling, 2014; Paul, Chakraborty, & Mandal, 2019; Raychaudhuri et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metals such as arsenic (As), mercury (Hg), cadmium (Cd), copper (Cu), chromium (Cr), lead (Pb), iron (Fe), manganese (Mn) and zinc (Zn) do not degrade and these metals could easily accumulate throughout the trophic chain and persist in nature (Borchert, Leaphart, Bryan, & Beasley, 2019; Burger, Mizrahi, Tsipoura, Jeitner, & Gochfeld, 2018; Vizuete et al, 2018); at the same time, As, Cd, Pb and Hg have no established biological functions and are considered as contaminants (Hejna et al., 2018). The presence of HMs has been registered in tissues of wild birds (Bond & Robertson, 2015; Burger et al., 2018; Majidi, Bahramifar, & Ghasempouri, 2015; Sepúlveda & Gonzalez‐Acuña, 2014), including the Andean condor (Di Marzio et al., 2018; Plaza et al, 2019; Wiemeyer et al., 2017). Due to the HM toxicity to different organisms, bacteria have developed some resistance mechanisms and have managed to persist in various highly contaminated locations, constituting possible biomarkers of environmental contamination (Di Cesare, Eckert, & Corno, 2016; Martins, Zanetti, Pitondo‐Silva, & Stehling, 2014; Paul, Chakraborty, & Mandal, 2019; Raychaudhuri et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Metals such as arsenic (As), mercury (Hg), cadmium (Cd), copper (Cu), chromium (Cr), lead (Pb), iron (Fe), manganese (Mn) and zinc (Zn) do not degrade and these metals could easily accumulate throughout the trophic chain and persist in nature (Borchert, Leaphart, Bryan, & Beasley, 2019;Burger, Mizrahi, Tsipoura, Jeitner, & Gochfeld, 2018;Vizuete et al, 2018); at the same time, As, Cd, Pb and Hg have no established biological functions and are considered as contaminants (Hejna et al, 2018). The presence of HMs has been registered in tissues of wild birds (Bond & Robertson, 2015; Burger Mandal, 2019;Raychaudhuri et al, 2007). These resistances include three known mechanisms against HM toxicity: complexation or sequestering of the HM; detoxification by sequestering of intracellular metal ions; and excretion of the HM by efflux systems (Nies, 1999;Seiler & Berendonk, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…All statistical analyses were performed in R 3.4.2 (R Development Core Team ). For comparison purposes in Discussion , we assumed a moisture of 65% in red blood cells (Tartu et al ; Bond and Robertson ) and 79% in whole blood (Eagles‐Smith et al ) and that red blood cells consist of 45% of the whole blood, and that most Hg is accumulated in red blood cells (Bond and Robertson ).…”
Section: Methods  and Materialsmentioning
confidence: 99%
“…Previous studies demonstrated that Hg in blood is associated predominantly with the cellular fraction (i.e., RBCs) rather than plasma (Bond and Robertson 2015;). The vast majority (>90 %) of total Hg (THg) in seabird RBCs is MeHg Albert et al 2019), and the estimated half-life of Hg in the blood of great skuas (Stercorarius skua) is 30-60 days (Bearhop et al 2000c).…”
Section: Total Hg Analysismentioning
confidence: 99%